Language and Morality: An Analysis of Gabriel Okara’s The Voice - Baridisi Hope Isaac; Ishmael Ukie Gwunireama; Tamunosiki Victor Ogan (Pascasarjana Universitas Negeri Makassar, 2021)
Man’s perceptions or worldviews about reality are conditioned and shaped by the language in which they are expressed. Thus, our knowledge of morality is expressed in the language we use. This paper examines the interrelatedness of language and morality using the matrix of Gabriel Okara’s The Voice. It explores the relationship between language and morality, and how they feature in the actual state of affairs. It utilizes the method of textual analysis and hermeneutic phenomenology in carrying out the research. It concludes that language and morality are inseparably bound together. It recommends a reappraisal of Okara's conception of language and morality within the framework of African ethics.